The Exhibition and Characterization of Seven Salted Paper Prints. Issue 3 (1st October 2020) - Barro, Lisa; Sanderson, Katherine; Centeno, Silvia A.; Saunders, Beth
ABSTRACT: Seven salted paper prints from the 1840s and 1850s in the permanent collection of The Metropolitan Museum of Art were included in the exhibition, Paradise of Exiles: Early Photography in Italy, from March to August 2017. This investigation analyzed works by Giacomo Caneva; Firmin-Eugène Le Dien and Gustave Le Gray; and Calvert Richard Jones. The study also reviewed period photographic techniques with a focus on gold and "old hypo" toning. In addition to reflected light microscopy, analytical methods included X-ray fluorescence (XRF) and Raman spectroscopy. Silver, gold and sulfur were found in association with the image material in these prints. All seven paper substrates were found to contain blue pigment inclusions - either smalt or ultramarine. Measurements taken with a spectrophotometer and microfading tester (MFT) were used to study light sensitivity and real-time color-change behavior. Overall, color measurements indicated that the salted paper prints were relatively stable with the exception of one unusual, bright yellow corner in a Calvert Jones print that contained silver and iodine. A comparison of real-time spectrophotometer and microfading tester measurements indicate that these results do not always correlate for silver-based photographs and requires further research.